1991
DOI: 10.1152/ajpheart.1991.261.5.h1487
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cardiac output during diurnal changes of activity in rats

Abstract: Rat locomotor and feeding behavior varies on a diurnal basis; at night the animals actively forage and eat, whereas during the day they are more inactive and somnolent. At night, cardiac output is higher, presumably for enhanced perfusion of the active muscles to support increased metabolism and for enhanced perfusion of the digestive organs to support increased digestion and nutrient absorption. Conversely, it is hypothesized that during the daytime, blood flow to these two tissues is relatively low. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 16 publications
2
67
1
Order By: Relevance
“…The plasma volume, 2.97% of body weight (Delp et al, 1991;Davies and Morris, 1993), is 3.3 times the volume of the stomach lumen, 0.91% of body weight (Roth et al, 1993). Therefore, an amount of nitrite taken up from the stomach increases the plasma concentration only 0.3 times as much as it decreases the stomach lumen concentration.…”
Section: Figmentioning
confidence: 99%
“…The plasma volume, 2.97% of body weight (Delp et al, 1991;Davies and Morris, 1993), is 3.3 times the volume of the stomach lumen, 0.91% of body weight (Roth et al, 1993). Therefore, an amount of nitrite taken up from the stomach increases the plasma concentration only 0.3 times as much as it decreases the stomach lumen concentration.…”
Section: Figmentioning
confidence: 99%
“…This is in agreement with previous in vivo studies that have shown that cardiac output is greater in the dark phase for rats. 8 However, such studies did not investigate the intrinsic properties of the heart alone, where contractile performance in vivo was undoubtedly affected by external factors, such as sympathetic tone, in addition to the intrinsic sensitivity of the heart to its environment.…”
Section: Diurnal Variation In Cardiac Performance and Metabolismmentioning
confidence: 99%
“…Oscillations in cardiovascular functions are firmly established, including time-of-day-dependent fluctuations in blood pressure, heart rate, and cardiac output (9,10,31). Night shift work and frequent time zone changes result in a dissociation between this intrinsic timekeeping mechanism and the environment, which is associated with increased risk of adverse cardiovascular effects (such as myocardial infarction and sudden cardiac death) (5,15,33).…”
mentioning
confidence: 99%